Towards humanized English learning: AI tools and speaking outcomes among university students - Muhamad Rifqi Bakhtiar; Hendi Pratama; Seful Bahri; Rudi Hartono; Sri Wahyuni; Kurniawan Yudhi Nugroho; Treenuch Chaowanakritsanakul (EduLite: Journal of English Education, Literature and Culture, 2026)
The rapid advancement of artificial intelligence in higher education has significantly transformed English language teaching and learning processes. This study investigates the integration of humanizing pedagogy into AI-supported learning environments, particularly via platforms such as ChatGPT, Gemini, and Bing AI/Copilot, to enhance university students' speaking outcomes. Using a cross-sectional survey design involving 54 university students from Elementary School Teacher Education, Accounting, and English Education programs, data were collected via a structured questionnaire during May 2025 and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that while artificial intelligence provides efficient feedback and structured practice, the human element remains essential for creating an authentic and supportive instructional atmosphere. Students who perceived psychological benefits from AI use showed the strongest intention to continue using these tools (β = 0.368, p < 0.01), followed by learning effectiveness (β = 0.289) and technology usability (β = 0.241), with the model accounting for 61.4% of variance in adoption intention. This research provides practical implications for curriculum designers to incorporate humanized artificial intelligence strategies into English education programs to ensure more effective and empathetic classroom instruction.